Structural Performance of Translucent Concrete Façade Panels - Awetehagn Tuaum; Stanley Shitote; Walter Oyawa; Medhanye Biedebrhan (Advances in Civil Engineering)
Energy conservation is an emerging global issue for sustainable infrastructure development. The building sector energy demand accounts for approximately 34% of the world’s energy demand, and artificial lighting consumes around 19% of the total delivered electricity globally. Developing a new kind of building material that can reduce the demand for artificial lighting energy is vital. This research attempts to address such issues through the development of translucent concrete façade using locally available materials that can be used as energy-saving building material. Bulk density, compressive strength, and flexural strength of translucent concrete containing 2%, 4%, and 6% volume ratios of plastic optical fibers (POF) were studied. Moreover, the flexural toughness of translucent concrete façade panels integrating 6% volume ratio of POF was also investigated. The experimental results showed that using up to 6% volume ratio of plastic optical fibers had no adverse effect on the bulk density of translucent concrete. Translucent concrete specimens exhibited relatively lower compressive and flexural strengths compared to the reference concrete. However, it was evidently observed that the compressive strength of translucent concrete increased with increasing the volume ratio of POF. The flexural strength of translucent concrete was observed to decline with increase in the volume ratio of POF. Results demonstrated that translucent concrete panels have better flexural toughness, ductility, and energy absorption capacity than the reference concrete panel. The energy-saving, environmental conservation, and aesthetic and structural performance improvements stemming from the application of translucent concrete façade panel as architectural wall would foster the development of green and resilient buildings as well as contribute to sustainable construction.